Excess of blood eosinophils prior to therapy correlates with worse prognosis in mesothelioma - Willems, Mégane; Scherpereel, Arnaud; Wasielewski, Eric; Raskin, Jo; Brossel, Hélène; Fontaine, Alexis; Grégoire, Mélanie; Halkin, Louise; Jamakhani, Majeed; Heinen, Vincent; Louis, Renaud; Duysinx, Bernard; et al. (Frontiers in Immunology, 2023)
Background: Only a fraction of patients with malignant pleural mesothelioma (MPM) will respond to chemo- or immunotherapy. For the majority, the condition will irremediably relapse after 13 to 18 months. In this study, we hypothesized that patients’ outcome could be correlated to their immune cell profile. Focus was given to peripheral blood eosinophils that, paradoxically, can both promote or inhibit tumor growth depending on the cancer type. Methods: The characteristics of 226 patients with histologically proven MPM were retrospectively collected in three centers. Characteristics included overall survival (OS), progression-free survival (PFS), overall response rate (ORR) and disease control rate (DCR). The mean absolute eosinophil counts (AEC) were determined by averaging AEC data sets of the last month preceding the administration of chemo- or immunotherapy. Results: An optimal cutoff of 230 eosinophils/µL of blood segregated the cohort into two groups with significantly different median OS after chemotherapy (13 and 31 months above and below the threshold, p < 0.0001). The corresponding two-year OS rates were 24% and 59% in the AEC > 230/µL and AEC < 230/µL groups, respectively. Based on shorter median PFS (6 vs 20 months, p = 0.0001) and reduced DCR (60.9 % vs 42.9 % at 6 months), the response to standard chemotherapy was significantly affected in the AEC > 230/µL subset. Similar conclusions were also drawn from data sets of patients receiving immune checkpoint-based immunotherapy. Conclusion: In conclusion, baseline AEC > 230/µL preceding therapy is associated with worse outcome and quicker relapse in MPM.